Paramour Chemicals Co., Inc. production of furfural, methanol and furfuryl alcohol from bagasse - de la Cruz, Buenafe (College of Engineering, 1981)
Capacity: 4000 MT furfural, 4000 MT furfuryl alcohol, 950 MT methanol -- Plant area: 12,500 sq. m. -- Fixed capital investment: P 29,000,000 -- Total capital investment: P 35,000,000 -- Total manufacturing cost: P 22,000,000 -- Annual sales at maximum production: P 100,000,000 -- Annual profit: P 20,000,000 -- Return on investment: 44% -- Pay-out period: 1.5 years -- Break-even point: 3,000 kgs per day